Women Serving Life without the Possibility of Parole: The Different Meanings of Death as Punishment. Issue 3 (6th September 2016) - VANNIER, MARION
Abstract: This article draws on the written accounts of a self‐selected group of 48 women serving life without parole (LWOP) in California. In their testimonies, death takes on a symbolic form illustrated by the passing of time and the 'mortification' of the self (Goffman 1959, 1961). Their letters emphasise an embodied construction of death, provoked by ageing, illnesses, and medical neglect, as well as through the removal of motherhood and mothering. Through exploring the different, and nuanced, meanings ascribed to death by women serving LWOP, the article combats the cultural invisibility of this punishment and those who endure it.